Molecular components required for resting and stimulated endocytosis of botulinum neurotoxins by glutamatergic and peptidergic neurons. Issue 8 (2nd May 2013) - Meng, Jianghui; Wang, Jiafu; Lawrence, Gary W.; Dolly, J. Oliver
Abstract : Proteins responsible for basal and stimulated endocytosis in nerves containing small clear synaptic vesicles (SCSVs) or large dense‐core vesicles (LDCVs) are revealed herein, using probes that exploit surface‐exposed vesicle proteins as acceptors for internalization. Basal uptake of botulinum neurotoxins (BoNTs) by both SCSV‐releasing cerebellar granule neurons (CGNs) and LDCV‐enriched trigeminal ganglionic neurons (TGNs) was found to require protein acceptors and acidic compartments. In addition, dynamin, clathrin, adaptor protein complex‐2 (AP2), and amphiphysin contribute to the depolarization‐evoked entry. For fast recycling of SCSVs, knockdown and knockout strategies demonstrated that CGNs use predominantly dynamin 1, whereas isoform 2 and, to a smaller extent, isoform 3 support a less rapid mode of stimulated endocytosis. Accordingly, proximity ligation assay confirmed that dynamin 1 and 2 colocalize with amphiphysin 1 in CGNs, and the latter copurified with both dynamins from cell extracts. In contrast, LDCV‐releasing TGNs preferentially employ dynamins 2 and 3 and amphiphysin 1 for evoked endocytosis and lack the fast phase. Hence, stimulation recruits dynamin, clathrin, AP2, and amphiphysin to augment BoNT internalization, and neurons match endocytosis mediators to the different demands for locally recycling SCSVs or replenishing distally synthesized LDCVs.—Meng, J., Wang, J., Lawrence, G. W.Dolly, J. O., Molecular components required for resting and stimulated endocytosis of botulinum neurotoxins by glutamatergic and peptidergic neurons. FASEB J. 27, 3167–3180 (2013). www.fasebj.org